Production and Characterization of Antimicrobial Metabolites from Streptomyces rochei Strain SC1 against Multi-Drug-Resistant Escherichia coli - Chavan, Sanjay; Lad, Bhagvat; Kadam, Tukaram (Asian Journal of Biological and Life Sciences)
Objectives: Streptomyces rochei have ability to synthesize a variety of antimicrobial compounds which exhibit antibacterial, antifungal, and even anticancer activities. S. rochei may have ability to produce bioactive compounds which will be effective against MDR pathogens. Materials and Methods: In the present investigation bioactive compound producing S. rochei was isolated from forest soil and identified by 16S rRNA gene sequencing. The potent S. rochei strain was used for production of bioactive compound, the bioactive compound was extracted using ethyl acetate, n-butanol and chloroform. The bioactivity of crude compounds was checked against MDR E. coli strains. The MDR E. coli are well known for causing infections in humans viz. diarrhea, urinary tract infections, sepsis, meningitis and bloodstream infections. The bioactive compounds present in n-butanol extract were purified by using column chromatography. The fraction showing maximum antimicrobial activity against MDR E. coli was structurally elucidated using UPLC-UV-MS. The S. rochei was isolated from forest soil sample on SCA and identified by using 16S rRNA sequencing as Streptomyces rochei and it was deposited in GenBank under Accession No. PQ637672. Results: The n-butanol extract of S. rochei showed maximum inhibitory activity against MDR E. coli. The 3rd fraction showed maximum antimicrobial activity was characterized by UPLC-UV-MS. The purified compound being identified as 10-deoxymethynolide (C17H28O4) having mass 296.1993 and Decylubiquinol (C19H32O4) having mass 324.2306 from class Macrolide and Hydroquinone respectively. Conclusion: These compounds had showed growth inhibiting activity against MDR E. coli.
Keywords: Bioactive compound; Escherichia coli; Streptomyces rochei.